Porous Silicates Modified with Zirconium Oxide and Sulfate Ions for Alcohol Dehydration Reactions - Heriberto Esteban Benito; Ricardo García Alamilla; Juan Manuel Hernández Enríquez; Francisco Paraguay Delgado; Daniel Lardizabal Gutiérrez; Pedro García (Advances in Materials Science and Engineering)
Porous silicates were synthesized by a nonhydrothermal method, using sodium silicate as a source of silica and cetyltrimethylammonium bromide as a template agent. Catalysts were characterized using thermogravimetric analysis, N2 physisorption, X-ray diffraction, FTIR spectroscopy, pyridine adsorption, potentiometric titration with n-butylamine, scanning electronic microscopy, and transmission electronic microscopy. The surface area of the materials synthesized was greater than 800 m2/g. The introduction of zirconium atoms within the porous silicates increased their acid strength from −42 to 115 mV, while the addition of sulfate ions raised this value to 470 mV. The catalytic activity for the dehydration of alcohols yields conversions of up to 70% for ethanol and 30% for methanol.